HEALTH STATUS OF POST-PARTUM ETAWAH CROSSBRED GOATS FED SILAGES AT THEIR LATE PREGNANCY - I W. D. P., PUTRA; DOLOKSARIBU, L.; KAYANA, I. G. N. (Majalah Ilmiah Peternakan; Vol 27 No 3 (2024): Vol. 27 No. 3 (2024)DO - 10.24843/MIP.V27.i03.p07, 2024)
This study was to determine the effect of feeding silages at late pregnancy to day-60 post-partum on health status of PE goats reared in Lemukih Village, Bali. This research was conducted from July to October 2023. Rando- mized block design consisting of four feeding treatments: Forage (T0), Forage+Soybean Husk Silage (SHS) (T1), Fo- rage+Brewer’s Spent Grain Silage (BSGS) (T2), and Forage+Odot Silage (OS) (T3), and three groups of bodyweights of goats. Variables observed were FAMACHA© score, endo-parasites, and erythrocytes level. The results, the goats were infected by Haemonchus spp., Eimeria spp., Trichostrongylus spp., and Ostertagia that dropped erythrocyte level below the standard 1.9 ± 0.39 (106 /?L). T3 goats tended to be infected by more endoparasites 906.7 ± 0.491 EPG with moderate infection, FAMACHA© score tended to be higher 1.5 ± 0.18, also tended to have lower erythroc- yte level 1,0 ± 0,39 (106 /?L). Contrastly, T1 goats tended to be infected by lesser endoparasite 200.0 ± 0.491 EPG. This proved that feeding SHS enabled T1 goats consuming the highest quantity and quality nutrient containing 0.34 kg crude protein, 4.64 kg TDN, with 0.06 kg kcal. In summary, feeding SHS improved health status of the goats by showing their FAMACHA© score, endoparasite, and erythrocyte level.